Revealing serum lipidomic characteristics and potential lipid biomarkers in patients with POEMS syndrome - Zhao, Hao (J Cell Mol Med, 2021)
POEMS syndrome is a rare plasma cell dyscrasia with distinct lipid metabolism abnormalities at disease onset. However, the serum lipidomic characteristics in patients with POEMS syndrome were not investigated. The study performed an untargeted lipidome screening by liquid chromatography‐tandem mass spectrometry (LS‐MS/MS) in the pre‐ and post‐treatment serum of 24 patients with POEMS syndrome, together with the serum of 24 paired healthy controls. Patients with POEMS syndrome had a distinct serum lipid composition compared with healthy controls, and a 3‐lipid model had a predictive accuracy of 93.5% in distinguishing patients and healthy controls consisting of fatty acyl 17‐oxo‐20Z‐hexacosenoic acid, phosphatidylcholine(16:0/18:1(9Z)) and sterol lipid 5b‐pregnanediol. Four lipids including 17‐oxo‐20Z‐hexacosenoic acid (r = 0.423, P = .040) were correlated with risk stratification, and 2 lipids including Cer(d18:0/13:0) were inversely related to serum vascular endothelial growth factor level (r=−0.465, P = .022). Eleven lipids were related to disease activity, including arachidonic acid which was inversely related and lysoPC(20:4) which was positively related. The study indicated a distinct lipid characteristic profile of patients with POEMS syndrome different from healthy controls and identified several lipids that may serve as potential diagnostic markers and monitors of therapeutic efficacy, as well as indicating potential metabolism pathways involved in the pathological process.